2018
DOI: 10.1089/lgbt.2017.0092
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Medical Doctors' Intentions to Discriminate Against Transgender Patients in Kuala Lumpur, Malaysia

Abstract: Purpose: Transgender people are frequent targets of discrimination. Discrimination against transgender people in the context of healthcare can lead to poor health outcomes and facilitate the growth of health disparities. This study explores factors associated with medical doctors' intentions to discriminate against transgender people in Malaysia. Methods: A total of 436 physicians at two major university medical centers in Kuala Lumpur, Malaysia, completed an online survey. Sociodemographic characteristics, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 40 publications
(57 reference statements)
0
44
0
5
Order By: Relevance
“…Despite this, little research exists that examines healthcare providers' attitudes toward adults with intellectual disabilities and the effects of those attitudes on the care of people with intellectual disabilities. Research findings on healthcare providers' attitudes about other vulnerable patient populations support the impact of negative healthcare provider attitudes on the patient–provider relationship (Chu & Galang, ; Hall et al, ; Parkinson, ), healthcare provider clinical decision‐making (Earnshaw et al, ; Vijay et al, ) and patient care seeking behaviours (Drainoni et al, ; van Loon, Knibbe, & Van Hove, ). However, these studies have not included adults with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 95%
“…Despite this, little research exists that examines healthcare providers' attitudes toward adults with intellectual disabilities and the effects of those attitudes on the care of people with intellectual disabilities. Research findings on healthcare providers' attitudes about other vulnerable patient populations support the impact of negative healthcare provider attitudes on the patient–provider relationship (Chu & Galang, ; Hall et al, ; Parkinson, ), healthcare provider clinical decision‐making (Earnshaw et al, ; Vijay et al, ) and patient care seeking behaviours (Drainoni et al, ; van Loon, Knibbe, & Van Hove, ). However, these studies have not included adults with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 95%
“…Despite multiple national reports calling attention to negative health‐care provider attitudes toward adults with ID in the United States, little research is found that examines how exactly health‐care providers' attitudes affect the care of people with disabilities in the present day. Research findings on health‐care providers' attitudes across vulnerable patient groups support the impact of negative health‐care provider attitudes on the patient‐provider relationship, health‐care provider clinical decision‐making, and patient care‐seeking behaviors . Only slightly over a decade ago, adults with disabilities described their perceptions of discriminatory health‐care provider attitudes and behaviors, including an unwillingness on the part of health‐care providers to adapt clinical routines to meet the needs of the person with a disability, the withholding of care or provision of inferior care, the separation of people with disabilities away from general patient areas, and insensitive provider communication with people with disabilities .…”
Section: Introductionmentioning
confidence: 96%
“…Although members of KP sub-groups may have different patterns of behaviour and social mixing that influence their HIV/STI risks, their vulnerabilities are augmented by common factors (Table 1). Often, KP experience structural barriers and societal discrimination that may increase their HIV/STI vulnerability by encumbering their access to healthcare [12][13][14][15][16][17]. Moreover, structural factors may not only directly affect susceptibility (e.g.…”
mentioning
confidence: 99%